173k views
5 votes
If f(x) = x + 1 and g(x) = 2x - 7, which expression is equivalent to [fog|(3)?

User Dkantowitz
by
4.8k points

1 Answer

3 votes

Answer and Step-by-step explanation:

First, we plug in the value of 3 for x in g(x), then we plug the answer os g(x) into the value of x in f(x).

g(3) = 2(3) - 7

Multiply 2 by 3, then subtract 7.

g(3) = 6 - 7

g(3) = -1

Now, we plug -1 for x in f(x).

f(g(3)) = f(-1) = -1 + 1

f(-1) = 0

The value of f(g(3)) is 0.

#teamtrees #PAW (Plant And Water)

User Zenpoy
by
5.3k points